Gender in South African newsrooms. (1st September 2016) - Bosch, Tanja
Academic research reveals a quantitative and qualitative underrepresentation of women in news production and content. This article presents findings of a qualitative study, exploring the experiences of women journalists in Cape Town, South Africa. Drawing on in-depth qualitative interviews, the research found that most journalists did not feel that their gender impacted daily newsroom routines, with many seeing their predominant coverage of 'soft' news items as a personal preference and not a structural constraint, even though they sometimes felt restricted by the dominance of normative news values. Concerns over personal safety were foregrounded, and some respondents highlighted the use of sexuality by women journalists to gain leverage with editors or sources. While the experiences of women journalists cannot be generalized, particularly since this study provides findings from a limited regional sample, it creates room for further studies in this area at national level and in other developing nations.